THE APPLICATION OF A COMBINATION OF WARM COMPRESSES AND SLOW STROKE BACK MASSAGE WITH OLIVE OIL IN REDUCING THE HEADACHE SCALE OF HYPERTENSIVE PATIENTS AT DR. GONDO SUWARNO HOSPITAL - Setiawan, Iwan Sulis; Rizal Ginanjar; Umi Margi Rahayu; Alvina Listiyani (Journal of Applied Health Management and Technology, 2025)
Background: The 2023 Indonesian Health Survey found that the prevalence of hypertension in the population aged >18 years was 30.8%. Hypertension is the leading cause of death worldwide. The initial symptoms of hypertension are asymptomatic, characterized only by an increase in blood pressure. Most people with hypertension complain of tight necks to headaches that create discomfort in the head area. Objective: To explain nursing care in hypertensive patients with warm compresses and slows stroke back massage in lowering the scale of headaches. Methods: This case study uses a descriptive method by applying an evidence-based practice that focuses on one of the nursing problems. Results: In a case study conducted on 3 respondents who experienced headaches due to hypertension by being given a combination of warm compresses and slow stroke back massage for 6 meetings, there was a decrease in pain scale. In Mrs. W, the initial pain scale was 4 after the intervention to a pain scale of 1. In Mr. K, the initial pain scale of 5 after the intervention became 1. In Mr. M, the initial pain scale was 4 after the intervention, the pain scale became 1. Conclusion: The application of a combination therapy of warm compresses and slow stroke back massage with olive oil is effective in reducing pain.Keywords: Warm Compress; Slow Stroke Back Massage; olive oil; headache; Hypertension.